2022
DOI: 10.3389/fmars.2022.993644
|View full text |Cite
|
Sign up to set email alerts
|

Extreme coastal water levels with potential flooding risk at the low-lying Saint Louis historic city, Senegal (West Africa)

Abstract: In a context of global warming characterized by a mean sea level rise and extreme meteorological events, the study of the causes for coastal flooding is essential to protect communities and ecosystems. Densely urbanized, and rather unprotected cities in developing countries such as the historic Saint Louis city in Senegal are particularly vulnerable to coastal flooding and sea hazards. From satellite-derived high resolution DEM and global ocean reanalyses, here we quantify the extreme coastal water level in or… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 56 publications
1
4
0
Order By: Relevance
“…In Saint-Louis (Senegal), Cisse et al found an increase in flood risk between 1994 and 2015 caused mainly by sea level rise. In the all, the general trend as shown in this study is that erosion rates has been increasing since 1980 up to the present [28].…”
Section: Discussionsupporting
confidence: 62%
“…In Saint-Louis (Senegal), Cisse et al found an increase in flood risk between 1994 and 2015 caused mainly by sea level rise. In the all, the general trend as shown in this study is that erosion rates has been increasing since 1980 up to the present [28].…”
Section: Discussionsupporting
confidence: 62%
“…As mentioned above, particularly in the introduction, there is no scientific information on topographic subsidence in Saint-Louis, particularly on the Langue de Barbarie. Yet this highly anthropized section of Senegalese coastline, established on a sandy facies with a low gradient, is extremely vulnerable to coastal hazards (erosion and coastal flooding) [29,30,[38][39][40][41] Today, in a context of climate change and the exploitation of oil and gas resources in Saint-Louis, a study focusing on the problem of coastal subsidence seems important. The topographic subsidence rates obtained clearly show that a large part of Saint-Louis is sinking downwards, which could have considerable impacts for an amphibious city like Saint-Louis, marked by its openness to the Atlantic coast and the presence of the river.…”
Section: Discussionmentioning
confidence: 99%
“…The Saint-Louis coastline, particularly the Langue de Barbarie, is highly vulnerable to the risk of coastal flooding induced by extreme weather and sea conditions in the context of climate change. According to [29,30], coastal flooding is one of the most serious threats to Saint-Louis. Again, according to these authors, this low sandy strip, the Langue de Barbarie, is sensitive to coastal hazards, particularly marine submersion, in that 88% of the territory of Gueth Ndar would be submerged, while 68 and 69% of the districts of Goxxu Mbathie and Ndar Toute would be below the water level induced by the centennial swell.…”
Section: Introductionmentioning
confidence: 99%
“…This would be very helpful locally, particularly for coastal managers and engineers. Although operational accuracy without a ground control point is not yet possible for coastal studies at this stage (as stated by [22,35,72]), the limitations in accuracy encountered suggest that satellite-based topography monitoring can be a significant advancement in overcoming long-standing technological barriers in monitoring, thereby supporting local coastal engineering and coastal monitoring. By offering local perspectives, this study offers valuable insights for developing evidence-based measures to minimize damage and injury.…”
Section: Discussionmentioning
confidence: 99%